Cost-Efficient Ag/Ag-TiO2 Coating-Based Flexible Transparent Heat Reflector for Energy-Saving Smart Windows - Hazra S.; Dahiya S.; Bijarniya J.P.; Pramanik S.; Sarkar J.; Pal B.N. (My University, 2025)
This work has demonstrated a mass-producible and low-cost transparent heat reflector (THR) fabrication method on a flexible substrate by using a per-deposited silver nanostructure thin film which was grown in a two-step deposition method. Initially, a polycrystalline Li4Ti5O12 (LTO) thin film was grown on a plastic substrate by a low-temperature processed sol-gel technique. Afterward, mobile Li+ of the LTO thin film was replaced by Ag+ by an ion-exchange method to form the Ag-TiO2 thin film. In the second step, 10 nm of Ag was deposited on top of the Ag-TiO2 thin film by thermal evaporation. This bilayer THR has IR/NIR reflectivity of ∼85-90% in combination with its visible transmittance of ∼50-70%. For higher environmental stability of this THR, a polymer film (PMMA) was coated on top of this Ag/Ag-TiO2 coating. To realize the practical application of this THR, a prototype box with one transparent glass window coated with this THR film was developed, and its internal temperature was investigated during the daytime. A reduction of internal temperature of ∼6-7 °C was observed due to this THR coating with respect to the reference uncoated box, indicating its plausibility as an energy-saving smart window application. © 2024 American Chemical Society.